2021
DOI: 10.3389/fneur.2021.713018
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Inflammatory Markers in Subacute Stroke Are Associated With Clinical Outcome but Not Modified by Aerobic Fitness Training: Results of the Randomized Controlled PHYS-STROKE Trial

Abstract: Background: Inflammatory markers, such as C-reactive Protein (CRP), Interleukin-6 (IL-6), tumor necrosis factor (TNF)-alpha and fibrinogen, are upregulated following acute stroke. Studies have shown associations of these biomarkers with increased mortality, recurrent vascular risk, and poor functional outcome. It is suggested that physical fitness training may play a role in decreasing long-term inflammatory activity and supports tissue recovery.Aim: We investigated the dynamics of selected inflammatory marker… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Inflammatory markers, such as C-reactive protein, interleukin-6, tumor necrosis factor, and fibrinogen, are up-regulated following acute stroke. The associations of these biomarkers with increased mortality, recurrent vascular risk, and poor functional outcome of stroke have been reported ( Whiteley et al, 2011 ; Mobarra et al, 2019 ; Kirzinger et al, 2021 ). Therefore, we speculate that UA may cause recurrence of ischemic stroke through inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory markers, such as C-reactive protein, interleukin-6, tumor necrosis factor, and fibrinogen, are up-regulated following acute stroke. The associations of these biomarkers with increased mortality, recurrent vascular risk, and poor functional outcome of stroke have been reported ( Whiteley et al, 2011 ; Mobarra et al, 2019 ; Kirzinger et al, 2021 ). Therefore, we speculate that UA may cause recurrence of ischemic stroke through inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In ammatory markers such as IL-1, IL-6, CRP, TNF-α, and brinogen are upregulated in AIS. [17] Studies have also associated these in ammatory markers with increased mortality, recurrent vascular risk, and poor functional outcome. [15] They have been suggested to cause injury to vascular endothelial cells, promote the release of in ammatory factors, and activate the coagulation cascade that can lead to further expansion of the infarct core after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[3,[20][21][22][23] The most studied in ammatory cytokines in AIS are the pro-in ammatory cytokines IL-1β, Il-6, and TNF-α. [9,17] In this study, we did not include TNF-α because the increasing trend of TNF-α, IL-1β, and IL-6 was consistent; for example, a previous study showed within 72 h of neurological sign onset, in a 1month follow-up period, they assessed NIHSS as primary and plasma levels of TNF-α, IL-1α, IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12p70, IFN-γ, IP-10, MCP-1, 8-isoprostane were increased. The levels of plasma in ammatory markers TNF-α, IL-1β, IL-6, IL-8, and prostaglandin E2 P were signi cantly decreased in a therapy group after 7 days of intervention, [24] but the in ammatory factors IL-1β and IL-6 were increased signi cantly in cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, those predisposed to lower IL‐6 production also showed greater sIL6R levels 52 . Some research shows higher IL‐6 serum levels at study enrollment correlate to worse outcomes at 3 and 6 months (NCT01953549) 53 . Elevations in IL‐6 at least 3 weeks after initial lacunar stroke predict recurrent vascular events, such as stroke, vascular death, and myocardial infarction 54 .…”
Section: Clinical Milestonesmentioning
confidence: 99%